2014
DOI: 10.1007/s00381-014-2403-x
|View full text |Cite
|
Sign up to set email alerts
|

SHH, WNT, and NOTCH pathways in medulloblastoma: when cancer stem cells maintain self-renewal and differentiation properties

Abstract: Our results suggest the presence of activated developmental signaling pathways in MB, which are important for cell proliferation and maintenance, and that may be targeted for novel therapeutic options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…This supports a similar finding by other investigators 10 11 who demonstrated that high Hh/Shh expression was significantly correlated with unfavorable prognostic factors. These results are consistent with most published reports that increased Shh expression is correlated with advanced stage cancers in gastric 26 , prostate 27 , medulloblastoma 28 and breast (Reviewed by) 29 . These results reinforce our claim that the Shh signaling activation loop is functioning to promote breast tumor formation, progression and proliferation.…”
Section: Discussionsupporting
confidence: 93%
“…This supports a similar finding by other investigators 10 11 who demonstrated that high Hh/Shh expression was significantly correlated with unfavorable prognostic factors. These results are consistent with most published reports that increased Shh expression is correlated with advanced stage cancers in gastric 26 , prostate 27 , medulloblastoma 28 and breast (Reviewed by) 29 . These results reinforce our claim that the Shh signaling activation loop is functioning to promote breast tumor formation, progression and proliferation.…”
Section: Discussionsupporting
confidence: 93%
“…The WNT pathway, Notch signaling and Hedgehog signaling pathway are known to regulate the self-renewal of normal stem cells. 33,34 Sam68 is an RNA binding protein with Src homology (SH) 2 and 3 domain binding sites, and can be coprecipitated with p85 PI3K. 35 AKT can activate beta-catenin by inhibiting GSK3beta.…”
Section: Discussionmentioning
confidence: 99%
“…Deregulation of Wnt signaling has been shown to stimulate proliferation and maintenance of CSC populations in many cancers including colorectal cancer, hepatocellular carcinoma, medulloblastoma, and some leukemias (Cordeiro, et al, 2014, Dong, et al, 2016, Dow, et al, 2015, Petropoulos, et al, 2008, Wang, et al, 2016). However, studies in NB have shown conflicting evidence for the role of the Wnt pathway in tumorigenesis.…”
Section: Neural Crest Development and Nbmentioning
confidence: 99%